PENGGEMBALAAN SEBAGAI MANIFESTASI ANUGERAH ALLAH: Studi Teologis–Eksegetis terhadap Yohanes 21:15–17 - Gerbin Tamba; Janes Sinaga; Juita Lusiana Sinambela (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2025)
Shepherding constitutes a central dimension of church life; however, it is frequently reduced to administrative and functional roles in contemporary practice. This study critically examines shepherding as a manifestation of God’s grace through a theological–exegetical analysis of John 21:15–17. Employing a qualitative approach, this research integrates biblical exegesis with a lexical analysis of key Greek terms, particularly ἀγαπάω, φιλέω, and ποιμαίνω, to explore the theological foundation of pastoral ministry. The findings demonstrate that shepherding is not grounded in human competence or institutional authority but in a relationship of love initiated and sustained by divine grace. The pastoral mandate given to Peter reflects a grace-centered dynamic in which love becomes the essential basis for responsibility. Furthermore, shepherding is understood as a continuous and holistic vocation encompassing nurturing, guiding, protecting, and teaching the congregation. This study contributes to pastoral theology by offering an exegetically grounded and theologically integrated framework that interprets shepherding as a manifestation of God’s grace. It also provides a conceptual foundation for contemporary pastoral ministry to embody Christ-centered leadership rooted in relational love and divine initiative.